Reconstructing eruptions at a data limited volcano: a case study at Gede (West Java) - Tennant, Eleanor (2022)
Understanding past eruption dynamics at a volcano is crucial for forecasting the range of possible future eruptions and their associated hazards and risk. In this work we use numerical models to recreate the footprints of pyroclastic density currents (PDCs) and tephra fall from three eruptions at Gede volcano, Indonesia, with the aim of gaining further insight into these past eruptions and identifying suitable eruption source parameters for future hazard and risk assessment. Gede has the largest number of people living within 100 km of any volcano worldwide, and has exhibited recent unrest activity, yet little is known about its eruptive history. For PDCs, we used Titan2D to recreate geological deposits dated at 1.2 and c. 1 kyrs BP. An objective and quantitative multi-criteria method was developed to evaluate the fit of 342 model simulations with field observations. In recreating the field deposits we were able to identify the best fitting values to reconstruct these eruptions. We found that the 1.2 kyrs BP geological deposits could be reproduced with Titan2D using either a dome-collapse or a column-collapse as the triggering mechanism, although a relatively low basal friction angle of 6° would suggest that the PDCs were highly mobile. For the 1 kyrs BP PDC, a column-collapse mechanism and a higher basal friction angle were required to fit the geological deposits. In agreement with previous studies, we found that Titan2D simulations were most sensitive to the basal friction angle parameter. We used Tephra2 to recreate historic observations of tephra dispersed to Jakarta and Gunung Patuha during the last known magmatic eruption of Gede in 1948. In the absence of observable field deposits, or detailed information from the published literature, we stochastically sampled eruption source parameters from wide ranges informed by analogous volcanic systems, allowing us to constrain the eruption dynamics capable of dispersing tephra to the most populous city in Indonesia, Jakarta. Our modelling suggests that the deposition of tephra fall in Jakarta during the November 1948 eruption was a very low probability event, with a < 1% chance of occurrence. Through this work, we show how the reconstruction of past eruptions with numerical models can improve our understanding of past eruption dynamics, when faced with epistemic uncertainty. At Gede volcano, this provides a crucial step towards the reduction of risk to nearby populations through volcanic hazard assessment.